2007
DOI: 10.1111/j.1600-0420.2007.00942.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of short‐term exposure of triamcinolone acetonide on fibroblasts and retinal pigment epithelial cells

Abstract: ABSTRACT.Purpose: We investigated the effects of short-term exposure to triamcinolone on cultured choroidal fibroblast (CFB) cells and retinal pigment epithelial (RPE) cells. Methods: To evaluate the effect of triamcinolone on cell proliferation, CFB and RPE cells were divided into three groups: a short-term exposure group; a longterm exposure group, and a non-treated control group. Cells in the shortterm exposure group were briefly exposed (5, 15 or 30 mins) to triamcinolone (0.01 mg ⁄ ml, 1 mg ⁄ ml or mitomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…Furthermore, it was shown that triamcinolone may have a toxic effect on RPE cells, although its anti-inflammatory and antiangiogenetic properties may to beneficial to avoid side effects of the PDT treatments. 12,13 All of these factors may contribute to the less favourable BCVA outcomes in the combination group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was shown that triamcinolone may have a toxic effect on RPE cells, although its anti-inflammatory and antiangiogenetic properties may to beneficial to avoid side effects of the PDT treatments. 12,13 All of these factors may contribute to the less favourable BCVA outcomes in the combination group.…”
Section: Discussionmentioning
confidence: 99%
“…Triamcinolone acetonide is a long acting glucocorticoid, which not only inhibits collagen synthesis but also accelerates collagen degradation, in addition to its ability to repress inflammation [16], also glucocorticoids have hindering effects of tumor lymphangiogenesis [17]. Sclera therapy is commonly the preferred treatment method for vascular malformations [18].…”
Section: Discussionmentioning
confidence: 99%
“…Cellular uptake efficiency was investigated using fluorescein isothiocyanate labeled DA-Chit (FITC/DA-Chit) nanoparticles, instead of TAA/DA-Chit nanoparticles, by both inverted fluorescence microscopy and flow cytometry. According to the literature, 16 proliferative vitreoretinopathy can be characterized by a proliferation of retinal pigment epithelial cells. Therefore, downregulation of VEGF mRNA expression by TAA/DA-Chit nanoparticles was assessed via real-time reverse transcription polymerase chain reaction (RT-PCR) in human retinal pigment epithelial cells through the controlled release of TAA.…”
Section: Introductionmentioning
confidence: 99%
“…10 This process is usually associated with several undesirable complications, including glaucoma and endophthalmitis. 16,17 Controlled release of this corticosteroid is thus important in achieving a sustained pharmacologic effect and overcoming the drawbacks of the procedure.…”
Section: Introductionmentioning
confidence: 99%